Caesarean scar defect: Risk factors and comparison of evaluation efficacy between transvaginal sonography and magnetic resonance imaging. (November 2019) - Tang, Xiaoyan; Wang, Jue; Du, Yan; Xie, Meng; Zhang, Hongwei; Xu, Heyang; Hua, Keqin
Abstract: Objectives: To determine the risk factors for development of caesarean scar defect (CSD), compare the efficacy of transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) for CSD assessment, and investigate the association between CSD size and clinical symptoms. Study design: One hundred and eighty-nine women with CSD and 378 women without CSD with a history of caesarean section (CS) at the Obsterics and Gynaecology Hospital of Fudan University between January 2008 and February 2016 were enrolled. The potential risk factors for CSD were investigated using multivariate logistic regression analysis. TVS and MRI were performed for CSD measurements, including residual myometrial thickness, and depth, length and width of CSD. Associations between CSD size by TVS/MRI and symptoms were evaluated. Results: CS time ≥85 min, peripartum fever or infection, and retroflexed uterus were risk factors for CSD, and age at last CS < 30 years, intraoperative blood loss <150 ml and double-layer closure were protective factors for CSD. Prolonged menstruation, dysmenorrhoea, chronic pelvic pain and infertility were the main clinical manifestations. Women with a larger CSD presented with more prolonged menstruation. Compared with TVS, measurements by MRI showed better prediction of the clinical symptoms of CSD. Conclusions: Various factors contribute to the development of CSD. Prevention of peripartum infection, reduction of CS time, reduction of blood loss and more careful uterine closure are needed to decrease the risk of developing CSD. MRI is a reliable method for the diagnosis and measurement of CSD, and can be utilized in clinical practice.